Elekta ONCENTRA 4.3 vs. MONACO 5.0.04: A comparison between 3DCRT DOSE calculation algorithms. (September 2016) - Torresin, A.; Cadioli, C.; Brambilla, M.G.; Monti, A.F.; Carbonini, C.; Ferrari, M.B.; Rottoli, F.; Zanni, D.; Alberta, G.
Abstract : Introduction: Each treatment planning system (TPS) must be accurately commissioned before its clinical use. Calculated and measured dose distributions have to be compared in different irradiation conditions. Purpose: In this work, we verified the degree of similarity between 3DCRT dose distributions calculated by two different TPSs produced by the same company. Materials and methods: Elekta Oncentra 4.3 and Monaco 5.0.04 dose distributions were analyzed to investigate the performances of their nominally identical calculation algorithms. A software provided by Elekta Support was used. Three different energy beams from an Elekta Synergy, equipped with MLCi, were investigated. Calculated depth dose curves, profiles and absolute dose were compared with measured data. ESTRO booklet 7 criteria were applied. For relative data, the gamma-index confidence limit was the reference analysis parameter; for absolute doses, the percentage difference between calculated and measured values was considered. Tolerances were adapted to irradiation geometry complexity. Results: In homogeneous phantom, the two systems showed a similar behavior, except in some particular situations for high energy beams. In particular, percentage dose differences between calculations and measurements were greater than tolerances for high energy small size fields in both systems. In inhomogeneous phantom, the two systems generated approximately the same results. Conclusion: Both TPSs can be considered adequate for clinical use for low and medium energies. For high energy, particular fields should be accurately tested and a Monaco reprocessing could be useful. For low and medium energy beam, a new processing could be helpful to improve Monaco behavior in profile tails. Disclosure: No relationships to disclosure.